Bioprospecting of Potential Microorganisms as Agents for Biodiesel Production from Sago Pulp Waste Feedstock - Lethulur, Alice Chaela; Seumahu, Cecilia Anna; Apituley, Edwin Thomas (Jurnal Biodjati, 2025)
The rising global energy demand and environmental issues associated with fossil fuel use have accelerated interest in renewable alternatives, such as biodiesel. This study aimed to provide a preliminary screening of potential indigenous microorganisms among isolates with high ability to saccharify lignocellulosic sago pulp waste, an abundant, non-food biomass in Maluku, and to accumulate lipids. Laboratory experiments were conducted to isolate, characterize (macro- and microscopically), saccharify, and accumulate lipids. Bacterial isolates were evaluated for saccharification ability using two parameters: the cellulolytic index (CI), determined by the clear zone on solid CMC media, and reducing sugar production in modified liquid CMC media using pretreated sago waste, measured by Benedict’s test. Yeast and mold isolates were assessed for lipid accumulation through Sudan Black B staining and gravimetric lipid extraction under nitrogen-limited conditions. Results identified four bacterial isolates capable of saccharification, with isolate BAS 1B showing the highest cellulolytic index, and all isolates produced detectable reducing sugars by Benedict’s test. All yeast and mold isolates accumulated intracellular lipids, with YAS 2 and KAS 2 isolates accumulating the highest lipid compared to the positive control (Saccharomyces cerevisiae). As this study was based on a single-point observation (n=1), the results are exploratory and should be interpreted cautiously. Nevertheless, isolates BAS 1B, YAS 2, and KAS 2 show promising potential for further biodiesel-related research using lignocellulosic waste. Further studies with replication and quantitative validation are required prior to any industrial consideration